4 - Re-membering Wangari Maathai’s Feminist Scholarship in her Autobiography Unbowed: One Woman’s Story - Mutie, Stephen M. (Journal of Higher Education in Africa, 2022)
While scholars have proposed to interrupt and resist the prevailing androcentric view prevalent in Kenyan society, and, of course, some of these ways have borne fruit, this article proposes to turn attention to women’s narratives as captured in their autobiographies. This article is thus an interpretive analysis of Professor Wangari Maathai’s autobiography Unbowed: One Woman’s Story. Hopefully, personal story will answer particular theoretical questions that underpin the understanding and conceptualisation of feminism by Wanjiku (poor women) in Kenya. Under the backdrop of this question lies a fundamental assumption that feminism in Kenya needs a rethinking and a possible reconceptualisation to address past failures and setbacks. While locating its interrogation on postcolonial feminist theoretical underpinnings, the article adopts a qualitative approach as part of the research design. Being interpretive, the study relies on lit-crit methodology to analyse Wangari Maathai’s Unbowed. The main concern is to interrogate how Maathai’s autobiography reframes feminist scholarship in Kenya, particularly by underscoring the significance of Wanjiku as a key resource in the whole feminist enterprise.